INDONESIAN EXPERIENCE IN STUDYING CAPITAL STRUCTURE OF REAL ESTATE FIRMS: APPLYING FINANCE THEORY TO SUPPLY CHAIN MANAGEMENT - Septian, Septian; Sriyono, Sriyono; Tanzil Multazam, Mochammad (International Journal of Supply Chain Management, 2019)
the real estate is a fast-growth and dynamic industry. Firms that operate in this field need capital. The purpose of this research is to reinforce the capital structure of firms listed on the stock exchange in Indonesia. This study uses a multiple linear regression analysis technique. The analysis revealed that profitability, growth and leverage are negatively related to capital structure. The conclusion is that firms have to reinforce their capital structure, to control profitability and operation. The research results show that stock exchange specialists can have wider opportunities with the light thrown on financial issues relating to supply chain management.